Antibody responses to tick-borne encephalitis virus non-structural protein 1 and whole virus antigen–a new tool in the assessment of suspected vaccine failure patients. Issue 1 (1st January 2019) - Albinsson, Bo; Rönnberg, Bengt; Vene, Sirkka; Lundkvist, Åke
ABSTRACT: We report a new tool for improved serological diagnostics in suspected tick-borne encephalitis (TBE) vaccine failure cases. Due to an increase in the incidence of disease as well as the number of vaccinees, specific and simplified diagnostic methods are needed. Antibody responses to TBE-virus (TBEV) non-structural protein 1 (NS1) are detectable post TBEV infection but not post vaccination. We have used samples from 14 previously confirmed Swedish TBEV vaccine failure patients to study antibody responses against NS1 and whole virus antigens, respectively. Our conclusion is that the detection of antibodies directed to TBEV NS1 antigen is a useful tool to considerably simplify and improve the quality in investigations regarding suspected TBEV infection in vaccinated patients.